2018
DOI: 10.1016/j.ajoc.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of retinal pigment epithelial detachment secondary to exudative age-related macular degeneration

Abstract: PurposeThis pilot study evaluated the combination of photodynamic therapy (PDT) and anti-vascular endothelial growth factor (anti-VEGF) as a treatment in patients with a pigment epithelial detachment (PED) due to exudative age-related degeneration (AMD).MethodsWe analyzed seven consecutive patients between September 1, 2015 and September 1, 2017 with a PED secondary to exudative AMD who were treated with full fluence standard PDT and a series of monthly intravitreal anti-VEGF injections. Follow-up ranged betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…PED can occur in up to 62.7% of eyes with n-AMD [ 6 ]. The treatment for PED is unsatisfactory, although multiple anti-VEGF agents are available [ 23 ]. The previous study reported that the PED type, n-AMD subtype, baseline PED height, and anti-VEGF drug type were associated with the probability of PED resolution after anti-VEGF treatment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…PED can occur in up to 62.7% of eyes with n-AMD [ 6 ]. The treatment for PED is unsatisfactory, although multiple anti-VEGF agents are available [ 23 ]. The previous study reported that the PED type, n-AMD subtype, baseline PED height, and anti-VEGF drug type were associated with the probability of PED resolution after anti-VEGF treatment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are different types of fluids with regard to their position. Intra-Retinal Fluid (IRF) normally appears above Outer Plexiform Layer (OPL), Sub-Retinal Fluid (SRF) is dark accumulations of fluid beneath the Outer Segment Layer (OSL) [20] and Pigment Epithelial Detachments (PEDs) are related to a condition where the Retinal Pigment Epithelium (RPE) detaches from Bruch's Membrane due to the buildup of fluid or blood between these layers [21]. In this section, we have employed two distinct techniques to locate all kinds of fluids (Fig.…”
Section: Fluid Segmentation Tabmentioning
confidence: 99%
“…Jako jedinou, v současné době schválenou léčbou dle SPC, je intravitreální anti-VEGF terapie. Dle probíhajících studií se dále jeví jako účinná kombinace fotodynamické terapie a anti-VEGF [9].…”
Section: úVodunclassified